Sustainable Drying Technologies - del Real Olvera, Jorge (IntechOpen, 2016)
Sustainability should be a key component of every process of production, safeguarding resources and reserves for future generations. The primary goal of this book is to cover the state-of-the-art and future directions in sustainable drying technologies. This interdisciplinary and comprehensive volume, consisting of five chapters, covers a survey of trends in sustainable drying technologies for the development of functional foods, spray drying of juice, thermostability of freeze-dried for plants and evaporative drying of low rank coal. After reading this book, I am certain that you will find justified reasons to start your own personal and social awareness campaign in favour of these effective technologies.